Fat in the Fifties : America's First Obesity Crisis - Rasmussen, Nicolas, 1962- (Book collections on Project MUSE., 2019)
Fat in the Fifties is required reading for public health practitioners and researchers, physicians, historians of medicine, and anyone concerned about weight and weight loss.